THE CLEAN PRODUCTION CONCEPT AS A FOUNDATION FOR EMBRACING CORPORATE SOCIAL RESPONSIBILITY-A CASE STUDY CONDUCTED AT BASRA'S GENERAL COMPANY FOR PLASTIC INDUSTRIES - Author (AU) Manal Abdul Hameed Abdul Majeed (Scholars Digest Publishing, 2024)
Clean production is a philosophical and methodological approach that seeks to lessen the effects of industrial activity on the environment and achieve sustainable development. Corporate social responsibility is an extensive framework that seeks to attain a balance between the performance of the economy, society, and environment. Using a case study of the General Company for Plastic Industries in Basra, this study aims to comprehend the relationship between the adoption of corporate social responsibility and the clean production philosophy. A questionnaire created especially for this purpose was used to gather data from a sample of one hundred employees of the organization. The purpose of the questionnaire is to gauge how much staff members know about clean production and how it affects the social and environmental performance of the organization. The findings indicated that workers are becoming more conscious of the value of clean production and its advantages for society and the environment. The vast majority of participants confirmed that adopting clean production practices contributes to strengthening the image of the General Plastic Industries Company as a socially responsible company. The results also showed that the company has actually begun implementing some initiatives that enhance clean production, such as reducing resource consumption and recycling, which in turn contributed to improving operational efficiency and reducing costs. The study showed that there is a close connection between applying the clean production philosophy and embracing corporate social responsibility, since a company's ability to improve its environmental performance boosts consumer and local community trust, and thus improving the company's economic performance in the long term. The study recommends that the company should continue to adopt clean production practices and expand their scope to include all production processes, in addition to enhancing awareness and continuous training of workers to ensure the achievement of environmental and social goals. It also indicates the importance of cooperation with government agencies and civil society to support sustainable initiatives and contribute to achieving sustainable development in the region.
Keywords: clean production, social responsibility, environmental performance.